THE INFLUENCE OF COMPETENCE, CAREER DEVELOPMENT AND WORK ENVIRONMENT ON JOB SATISFACTIONEMPLOYEES AT BANK XYZ JAKARTA BRANCH - Bambang Wahyudi Wicaksono; Febian Reksa; Edi Wahyu Wibowo (RADJA PUBLIKA, 2025)
In 2020, the Covid-19 pandemic caused various problems at Bank XYZ, which could impact employee job satisfaction. This study aims to determine whether competency, career development, and the work environment simultaneously and partially significantly influence employee job satisfaction at the Jakarta branch of Bank XYZ. The research method used was associative research. Sampling was conducted using a purposive sampling technique.The sample taken was all employees of Bank XYZ Jakarta branch in sales, permanent employee status, excluding 62 management employees. Data analysis techniques used includes validity testingquestionnaire, testquestionnaire reliability, respondent profile analysis, descriptive analysis and multiple linear regression, coefficient of determination, F test and t test. Research resultsThe F-test shows that competence, career development, and work environment simultaneously have a significant effect on employee job satisfaction. The t-test results show that competence and work environment partially have a significant effect on employee job satisfaction, while career development does not have a significant effect on employee job satisfaction.